Cu-Deficient CuInSe Quantum Dots for “Turn-On” Detection of Adenosine Triphosphate in Living Cells - Chen, Jilei; Zhang, Lu; Li, Shulan; Jiang, Feng-Lei; Jiang, Peng; Liu, Yi (ACS applied nano materials, 2021)
Copper indium selenide (CISe) quantum dots (QDs) are a class of extremely appealing candidates for various biological applications due to their composition- and size-dependent photoluminescence and low toxicity. However, the synthesis of high-quality water-soluble CISe QDs with controlled composition in the aqueous phase is still a great challenge, which limits their biological applications. Moreover, the effects of the copper content in CISe QDs on the fluorescence and the corresponding mechanism are still subject to debate. Herein, a composition-tunable aqueous synthesis of high-quality Cu-deficient CISe QDs was presented, and the effects of the copper content on the fluorescence of CISe QDs was studied by the time-resolved fluorescence. The composition of CISe QDs could be flexibly controlled by manipulating the reaction temperature, the reaction time, and the Cu/In precursor ratio. The time-resolved fluorescence of CISe QDs with different Cu/In ratios suggested that the donor–acceptor pair (DAP) recombination was enhanced gradually with the increase of copper vacancies, resulting in the enhancement of fluorescence. However, if copper vacancies achieved an excessive concentration, the fluorescence would decrease possibly due to Auger recombination. The optimized CISe QDs with the maximum quantum yield of 10.3% were obtained with the Cu/In ratio, reaction temperature, and reaction time of 1/5, 170 °C, and 1 h, respectively. Based on the intense emission of the Cu-deficient CISe QDs, a highly sensitive “turn-on” fluorescent probe was developed for the detection of adenosine triphosphate (ATP) in living cells with a limit of detection of 56 nM. This work provides a paradigm for the aqueous-phase synthesis and applications of ternary I–III–VI QDs.